Characterization of Agrosystems in the Municipality of Gogounou in Northeast Benin by Medium-Resolution Remote Sensing - KINDJINOU, André; KOUMASSI, Dègla Herve; ETENE, CYR GERVAIS (My University, 2021)
Remote sensing is increasingly presented as a valuable tool for analyzing agrosystems, in addition to the approaches traditionally used. The present study aims to characterize the agrosystems of the commune of Gogounou from remote sensing data. The methodology developed consisted in using the time series of SPOT6 and SPOT7 images (6 m spatial resolution) acquired in the town of Gogounou and secondary data made up of the OSFACO project database and GPS points of 85 farms spread throughout the area. Mapping of the cultivated area was carried out using spectral indices derived from SPOT images. Three types of agricultural systems were identified: food crops (maize, millet, sorghum) representing 66% of agricultural areas, cash crops (cotton) for 13% of the sector and mixed crops (mixture of sorghum, millet and cotton) representing 21%. The results of this study make it possible to identify new avenues for coupling remote sensing and field data by providing continuous information over time on the characterization of agrosystems in Benin.
Keywords: Gogounou; mapping; agrosystem; remote sensing indices; crop area